Bacterial extracellular protein interacts with silver ions to produce protein-encapsulated bactericidal AgNPs. (July 2021) - Ashraf, Noreen; Ahmad, Fiaz; Lu, Yandu; Yin, Da-Chuan
Graphical abstract: Highlights: A bacterial extracellular protein efficiently reduces silver ions to AgNPs. Characterization of AgNPs confirmed they are encapsulated with protein molecules. Mechanism of interaction between Ag + and protein has been proposed. These AgNPs showed bactericidal activity to antibiotic resistant-bacteria. Abstract: Silver nanoparticles (AgNPs) have several applications in nanomedicine where the use of bacterial proteins for synthesis and capping of nanoparticles remain unstudied. Therefore, an extracellular protein of Enterobacter cloacae (SMP1) with ∼15.6 kDa size was partially purified and utilized for the synthesis of AgNPs. Synthesized AgNPs were detected by UV–vis spectrophotometer and characterized by dynamic light scattering (DLS), atomic force microscopy (AFM), cryo-scanning transmission electron microscopy (Cryo-STEM), and high-resolution transmission electron microscopy (HR-TEM). These AgNPs were monodispersed, spherical/quasi-spherical with zeta potential (ZP) of -26.9 mV with an average size of 58.75 nm measured by DLS. The encapsulation of AgNPs with protein was confirmed by electron elemental mapping and the potential mechanism of the synthesis of protein encapsulated AgNPs is outlined. These AgNPs showed broad spectrum bactericidal activity to clinical antibiotic-resistant bacteria. This study revealed that the extracellular protein of bacteria play a vital role in the synthesis of protein-encapsulated bactericidal AgNPs.